An association of secondary Al-Li-Be-Ca-Sr phosphates in the San Elías pegmatite, San Luis, Argentina - Galliski, Miguel Angel (2012)
The complex association of secondary phosphates from the Li-bearing, rare-element San Elías pegmatite in the Eastern Pampean ranges of Argentina shows widespread albite-hosted dendritic montebrasite in its northern part and lepidolite in the south. This dendritic montebrasite survived low-temperature processes virtually intact, but subrectangular blocks of montebrasite along the margins of quartz core were extensively modified in three stages: (i) two generations of secondary montebrasite intimately intergrown with hydroxylherderite, augelite, and fluorapatite, (acid hydrous fluids, locally channeled, at ∼450°-420°C, ∼2 kbar); (ii) goyazite-crandallite and hydroxylapatite formed after P-T equilibration between the pegmatite and its host rock along the path of metamorphic cooling, which introduced Ca, Sr and minor S from the host rocks into the pegmatite (at about <300°C); (iii) at a still lower T, the remainder of the primary montebrasite and all of its alteration products were subject to extensive leaching, removal and dispersal of phosphorus, and introduction of Si, generating pseudomorphs consisting mainly of kaolinite, quartz and minor lithian muscovite, K-feldspar (adularia), and traces of residual microlite as remnants of previous alteration stages.